Figurative Language Found in Lorde's "Virgin" Album - Ni Gusti Ayu Putu Ananda Devi; Desak Putu Eka Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study aims to analyze the use of figurative language in Lorde’s song lyrics using Knickerbocker and Reninger’s semantic theory. The research employs a descriptive qualitative method to identify and classify types of figurative language, including metaphor, simile, personification, hyperbole, paradox, and irony. A total of 13 data were found: 3 metaphors, 3 similes, 1 personification, 4 hyperboles, 1 paradox, and 1 irony. Each example was examined to understand its meaning and function in the lyrical context. The findings reveal that Lorde’s lyrics utilize figurative language not only to enhance poetic expression but also to convey themes of alienation, identity, and emotional complexity. These figures of speech reflect the songwriter's inner conflicts and societal observations. The study concludes that figurative language analysis provides deeper insight into modern song lyrics and their semantic richness.